2009
DOI: 10.1002/met.132
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the uncertainty in flood alerts driven by grand ensemble weather predictions

Abstract: ABSTRACT:The incorporation of numerical weather predictions (NWP) into a flood warning system can increase forecast lead times from a few hours to a few days. A single NWP forecast from a single forecast centre, however, is insufficient as it involves considerable non-predictable uncertainties and can lead to a high number of false or missed warnings. Weather forecasts using multiple NWPs from various weather centres implemented on catchment hydrology can provide significantly improved early flood warning. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 29 publications
2
89
0
Order By: Relevance
“…Figure 1 depicts the Upper Severn catchment, which is approximately 4062 km 2 , with urban, forest and agricultural land accounting for 3%, 7.1% and 48.5% of the area respectively, and loosely packed peat soil dominating the catchment. River levels are generally high in autumn and winter and low in summer (He et al, 2009). The observed discharge data were provided by the UK Environment Agency (EA) Midlands region and cover .…”
Section: The Upper Severn River Catchment Uk and Observed Datasetsmentioning
confidence: 99%
“…Figure 1 depicts the Upper Severn catchment, which is approximately 4062 km 2 , with urban, forest and agricultural land accounting for 3%, 7.1% and 48.5% of the area respectively, and loosely packed peat soil dominating the catchment. River levels are generally high in autumn and winter and low in summer (He et al, 2009). The observed discharge data were provided by the UK Environment Agency (EA) Midlands region and cover .…”
Section: The Upper Severn River Catchment Uk and Observed Datasetsmentioning
confidence: 99%
“…He et al (2009) were amongst the first to use TIGGE for flood warning. They used TIGGE ensemble forecasts to drive a coupled atmospheric-hydrological-hydraulic model system for a meso-scale catchment (4062 km 2 ) located in the Midlands region of England.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A prototype of such a system was successfully demonstrated by Pappenberger et al (2008) using seven weather centres in the European Flood Alert System (EFAS) to hindcast the October 2007 flood event in the Danube basin in Romania. A study carried out for a meso-scale catchment (4062 km 2 ) in the Midlands region of England set up a coupled atmospheric-hydrologic-hydraulic cascade system driven by TIGGE ensemble forecasts to produce a probabilistic discharge and flood inundation forecast (He et al, 2009). Both studies showed that the TIGGE database can produce an improved early flood warning of up to 10 days ahead.…”
Section: Introductionmentioning
confidence: 99%